قاعدة "درء الحدود بالشبهات" : دراسة مقاصدية - نقر، الطيب عبد الرازق (Kulliyyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2009)
This study focuses on the basic rule of dar' al-hudud bin al-shubuhat and its place in Islamic criminal law as well as in maqasid al-shari'ah. The noble companions of the Prophet (pbuh) have adopted this basic rule together with prominent Islamic scholars and imams, because it highlights the aspect of fairness and compassion in our esteemed shari'ah. Thus, if the judge has strong suspicions or doubt he must not implement the hadd out of mercy towards the suspect following the example of the Prophet (pbuh). This undertaking has paid special attention to three aspects to this basic rule which are: To establish the foundations of this legal basic rule; its function as an important element in Islamic jurisprudence, in addition to its implementation matters having to do with ones honour, soul, wealth, etc. Evidence and examples have been given for each segment of this study. In this study I have adopted a deductive, descriptive, analytical as well as comparative methodology. This is so because enforcing the basic rule provides us with guarantees that this deeply rooted maqasidi concept works for the safety of people, especially when the judge is in doubt. This research has arrived to the fact that dar' al-hudud bil shubuhat has an equivalent in man-made laws, which is: a suspect cannot be convicted if it is not established beyond a reasonable doubt that he committed a felony. This basic rule solidifies an important maqsadi objective which is convicting the real offender and staying away from doubt and suspicion. This confirms the concept of bara'at al-dhimmah in which a crime must be proven beyond reasonable doubt.